2x - 3x = -x
3x + 2x - 8x + 2x = -x
2x+3x = 5x
2x minus 3x is equal to -x.
6x2+ 35xy + 11y2=6x2+ 33xy + 2xy + 11y2= 3x(2x + 11y) + y(2x + 11y)= (2x + 11y)*(3x + y) 6x2+ 35xy + 11y2=6x2+ 33xy + 2xy + 11y2= 3x(2x + 11y) + y(2x + 11y)= (2x + 11y)*(3x + y) 6x2+ 35xy + 11y2=6x2+ 33xy + 2xy + 11y2= 3x(2x + 11y) + y(2x + 11y)= (2x + 11y)*(3x + y) 6x2+ 35xy + 11y2=6x2+ 33xy + 2xy + 11y2= 3x(2x + 11y) + y(2x + 11y)= (2x + 11y)*(3x + y)
(2x x 3x) x 2 = 12x (2x times 3x times 2)
sqrt(24x4) / sqrt(3x) = sqrt(24x4/3x) = sqrt(8x3) = sqrt(2x times 4x2) = 2x sqrt(2x) or (2x)1.5
(3x+1)(2x+4) = 6x2+4+2x+12x = 6x2+14x+4
Oh, dude, you're hitting me with some math here. So, when you multiply 2x squared by 3x squared, you just multiply the numbers (2 * 3 = 6) and add the exponents (2 + 2 = 4), giving you 6x to the power of 4. It's like algebra on steroids, man.
2x + 3x = 5x.
2x - 3x = -x
2x + 3x = 5x
2x-3x = -1
3x + 2x - 8x + 2x = -x
No. 3x plus 2x = 5x. 3x multiplied by 2x = 6x²
Sorry, need more info! is it 3 times 2x = 8?
If you mean: 3x-(2x+4x-6) then 3x-2x-4x+6 simplifies to 6-3x